Dopexamine attenuates endotoxin-induced microcirculatory changes in rat mesentery: role of beta2 adrenoceptors - Schmidt, Werner; Häcker, Axel; Gebhard, Martha-Maria; Martin, Eike; Schmidt, Heinfried (Critical care medicine, 1998)
Objective To investigate the influence of dopexamine on endotoxin-induced leukocyte adherence and on vascular permeability in postcapillary venules of rat mesentery. Design Randomized, controlled trial. Setting Experimental laboratory. Subjects Twenty-seven male Wistar rats, weighing 250 to 350 g. Interventions Rats received one of three treatments: a) Infusion of Escherichia coli endotoxin without dopexamine pretreatment; b) infusion of endotoxin with dopexamine pretreatment; or c) Infusion of endotoxin after pretreatment with dopexamine and ICI 118,551, a selective beta2-receptor antagonist. Measurements and Main Results Leukocyte adherence, red blood cell velocity, and vessel diameters in postcapillary venules were evaluated using in vivo videomicroscopy. Vascular permeability was determined by measuring the extravasation of fluorescence-labeled albumin. Venular wall shear rate was calculated from red cell velocity and vessel diameter. Dopexamine attenuated both the increase in leukocyte adherence and vascular permeability during endotoxemia. The attenuating effect on leukocyte adherence could not be antagonized by the beta2-adrenoceptor antagonist. However, the attenuating effect on vascular permeability was antagonized by ICI 118,551. Dopexamine prevented a decrease in venular wall shear rate during endotoxemia. This effect was not influenced by ICI 118,551. Conclusions Dopexamine attenuates endotoxin-induced microcirculatory disturbances in rat mesentery. The attenuating effect on vascular permeability is a beta2-adrenoceptor-mediated process, whereas the beta2-adrenoceptor actions of dopexamine play no significant role in attenuating leukocyte adherence. (Crit Care Med 1998; 26:1639-1645)